2020
DOI: 10.3390/cells9061334
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Plasma and Erythrocytes in Sickle Mice Points to Altered Nociceptive Pathways

Abstract: Few data-driven metabolomic approaches have been reported in sickle cell disease (SCD) to date. We performed a metabo-lipidomic study on the plasma and red blood cells of a steady-state mouse model carrying the homozygous human hemoglobin SS, compared with AS and AA genotypes. Among the 188 metabolites analyzed by a targeted quantitative metabolomic approach, 153 and 129 metabolites were accurately measured in the plasma and red blood cells, respectively. Unsupervised PCAs (principal component analyses) gave g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…For example, dysregulation of arginine metabolism 18 may constrain nitric oxide biosynthesis through substrate competition of arginase with endothelial nitric oxide synthase, thus limiting the vasodilatory capacity in SCD, with direct upstream regulatory effects on vaso-occlusive crisis, cardiovascular, cerebral and renal complications of SCD. [19][20][21][22][23][24] While most metabolomics studies in SCD have focused on plasma, a limited set of studies has investigated the RBC compartment. 11,20,22,25,26 These studies -always limited in sample size owing to technical constraints -suggested that depletion of glutamine, a precursor to glutathione, is a potential contributor to the increased susceptibility to hemolysis of the sickle erythrocyte, 26 owing to oxidant damage to proteins and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dysregulation of arginine metabolism 18 may constrain nitric oxide biosynthesis through substrate competition of arginase with endothelial nitric oxide synthase, thus limiting the vasodilatory capacity in SCD, with direct upstream regulatory effects on vaso-occlusive crisis, cardiovascular, cerebral and renal complications of SCD. [19][20][21][22][23][24] While most metabolomics studies in SCD have focused on plasma, a limited set of studies has investigated the RBC compartment. 11,20,22,25,26 These studies -always limited in sample size owing to technical constraints -suggested that depletion of glutamine, a precursor to glutathione, is a potential contributor to the increased susceptibility to hemolysis of the sickle erythrocyte, 26 owing to oxidant damage to proteins and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SCT has been established as a modest risk factor of venous thromboembolism among African Americans, but this risk is 1.5 to 2.0 fold greater in those with SCT compared to those without ( Austin et al, 2007 ; Folsom et al, 2015 ). While the mechanisms of metabolic reprogramming have been extensively investigated in humans ( Darghouth et al, 2011 ; Zhang et al, 2011 ; Wu et al, 2016 ) and mouse models of SCD ( Dembélé et al, 2020 ), to the best of the authors’ knowledge, literature is scarce or non-existent in the context of SCT, which is the focus of the present study.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dysregulation of arginine metabolism 19 may constrain nitric oxide biosynthesis through substrate competition of arginase with endothelial nitric oxide synthase, thus limiting the vasodilatory capacity in SCD, with direct upstream regulatory effects on vaso-occlusive crisis, cardiovascular, cerebral and renal complications of SCD. [20][21][22][23][24][25] While most metabolomics studies in SCD have focused on plasma, a limited set of studies has investigated the RBC compartment. 12,21,23,26,27 These studies-always limited in sample size owing to technical constraints-suggested that depletion of glutamine, a precursor to glutathione, is a potential contributor to the increased susceptibility to hemolysis of the sickle erythrocyte, 27 owing to oxidant damage to proteins and lipids.…”
mentioning
confidence: 99%